2006
DOI: 10.1002/bdm.545
|View full text |Cite
|
Sign up to set email alerts
|

Clouds make nerds look good: field evidence of the impact of incidental factors on decision making

Abstract: Abundant experimental research has documented that incidental primes and emotions are capable of influencing people's judgments and choices. This paper examines whether the influence of such incidental factors is large enough to be observable in the field, by analyzing 682 actual university admission decisions. As predicted, applicants' academic attributes are weighted more heavily on cloudier days and non-academic attributes on sunnier days. The documented effects are of both statistical and practical signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The authors also conduct experiments where subjects fill out questionnaires while seated in front of a computer whose screen saver eventually comes on, depicting either currency floating underwater (money prime) or fish swimming underwater (neutral prime). Exposure to floating bills reduces subjects' willingness to work in a 34 Simonsohn (2007Simonsohn ( , 2010 examines the impact of another pervasive prime: the weather. A laboratory study shows that priming subjects with images of clouds induces an academic mindset (Simonsohn 2007).…”
Section: Primingmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also conduct experiments where subjects fill out questionnaires while seated in front of a computer whose screen saver eventually comes on, depicting either currency floating underwater (money prime) or fish swimming underwater (neutral prime). Exposure to floating bills reduces subjects' willingness to work in a 34 Simonsohn (2007Simonsohn ( , 2010 examines the impact of another pervasive prime: the weather. A laboratory study shows that priming subjects with images of clouds induces an academic mindset (Simonsohn 2007).…”
Section: Primingmentioning
confidence: 99%
“…Exposure to floating bills reduces subjects' willingness to work in a 34 Simonsohn (2007Simonsohn ( , 2010 examines the impact of another pervasive prime: the weather. A laboratory study shows that priming subjects with images of clouds induces an academic mindset (Simonsohn 2007). Consequently, college admissions officers place more weight on academic credentials if they read applications on cloudy days (Simonsohn 2007), whereas prospective students are more likely to matriculate if they visit the school on a cloudy day (Simonsohn 2010).…”
Section: Primingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies suggest that people's senses and mood play important roles in decision-making processes (Cao and Wei, 2005;Simonsohn, 2007). Isen (1993), for example, found that when people felt good, their cognitive processes were simplified, thereby expediting their decision-making processes.…”
Section: Mood and Decisionsmentioning
confidence: 99%
“…Hirshleifer and Shumway (2003) reported that daily hours of sunshine were positively correlated with returns in the stock market. Simonsohn (2007) examined university admission decisions and found that applicants' academic attributes were weighted more heavily on cloudier days while non-academic attributes were weighted more heavily on sunnier days. Simonsohn (2010) also reported that cloudiness increased the appeal of academic activities.…”
mentioning
confidence: 99%